Effects of mutations in three domains of the vesicular stomatitis viral glycoprotein on its lateral diffusion in the plasma membrane [published erratum appers in J Cell Biol 1988 Jan;106(1):325] (The Rockefeller University Press, 1987)
The lateral mobility of the vesicular stomatitis virus spike glycoprotein (G protein) and various mutant G proteins produced by site- directed mutagenesis of the G cDNA has been measured. Fluorescence recovery after photobleaching results for the wild type G protein in transfected COS-1 cells yielded a mean diffusion coefficient (D) of 8.5 (+/- 1.3) X 10(-11) cm2/s and a mean mobile fraction of 75% (+/- 3%). Eight mutant proteins were also examined: dTM14, lacking six amino acids from the transmembrane domain; TA2, lacking an oligosaccharide in the extracellular domain; QN2, possessing an extra N-linked oligosaccharide in the extracellular domain; CS2, possessing a serine instead of a cysteine at residue 489 in the cytoplasmic domain, preventing palmitate addition to the glycoprotein; TMR-stop, lacking the entire cytoplasmic domain except an arginine at residue 483; and three chimeric proteins, G mu, G23, and GHA, containing in place of the 29 amino acid wild type cytoplasmic domain the cytoplasmic domains from the surface IgM from the spike protein of the infectious bronchitis virus or from the hemagglutinin protein of the influenza virus, respectively. The mean D for the mutant proteins varied over a relatively small range, with the slowest mutant, G23, exhibiting a value of 11.3 (+/- 1.4) X 10(-11) cm2/s and the fastest mutant, GHA, having a D of 28.6 (+/- 4.5) X 10(-11) cm2/s. The mean mobile fraction similarly varied over a small range, extending from 55 to 68%. None of the mutations resulted in the more rapid diffusion characteristic of membrane proteins embedded in artificial bilayers. Therefore, it appears that the cytoplasmic and transmembrane domains themselves contribute little to restraining the lateral mobility of this integral membrane protein when expressed in transfected cells.